Costimulatory signals potently modulate the T cell inhibitory capacity of the therapeutic CD11a antibody Efalizumab - Kuschei, Werner M (Clinical immunology (Orlando, Fla.), 2011)
Copyright © 2011 Elsevier Inc. All rights reserved.